2006
DOI: 10.1177/107424840601100107
|View full text |Cite
|
Sign up to set email alerts
|

Post-transplantation Lymphoproliferative Disorder in Heart and Kidney Transplant Patients: A Single-Center Experience

Abstract: Caucasian race and male gender were independent risk factors for developing PTLD. Pretransplant cytomegalovirus seropositive status is a strong predictor of developing PTLD. Management of PTLD requires randomized controlled trials of various chemotherapeutic and antiviral drugs regimens. Treatment of PTLD with rituximab is a beneficial alternative with a favorable outcome. Patients in whom primary Epstein-Barr virus, cytomegalovirus, or hepatitis C infection develop after transplantation should be managed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
38
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 5 publications
4
38
1
Order By: Relevance
“…3,15 Studies have shown that CMV-negative recipients who receive CMV-positive transplants have a relative risk of 1.489, and CMV-negative recipients who receive seronegative CMV donor organs have a relative risk of 2.036. 6,16 Four of the 10 patients in our study had this donor-negative/recipient-negative relation. However, if we focus on recipient CMV status alone, 7 of our patients had a CMV-negative status before transplant.…”
Section: Discussionmentioning
confidence: 97%
“…3,15 Studies have shown that CMV-negative recipients who receive CMV-positive transplants have a relative risk of 1.489, and CMV-negative recipients who receive seronegative CMV donor organs have a relative risk of 2.036. 6,16 Four of the 10 patients in our study had this donor-negative/recipient-negative relation. However, if we focus on recipient CMV status alone, 7 of our patients had a CMV-negative status before transplant.…”
Section: Discussionmentioning
confidence: 97%
“…[29][30][31][32][33][34][35][36][37] Treatment options for PTLD after heart transplant are not standardized, usually sequential, starting with a reduction in immunosuppression. In a prospective study including 13 heart transplant patients, aggressive reduction in immuno suppression (calcineurin reduction by 50% for 2 weeks and further 50% reduction for 1 week if not in complete remission), produced noncomplete remission and rejection was frequent.…”
Section: Discussionmentioning
confidence: 99%
“…Various multi-drug regimens such as CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone) have been used in PTLD patients (Wasson S et al, 2006;Elstrom RL et al, 2006;Taylor AL et al, 2006;Fohrer C et al, 2006;Buadi F et al, 2007;Patel H et al, 2007;Aversa SML et al, 2008) In spite of the high response rate up to 70%, the associated toxicity is significant and includes treatment-related deaths in about 25% of patients. The high mortality of the standard chemotherapy regimens in the PTLD population might occur because of various factors including baseline pharmacologic immunosuppression, graft dysfunction, and colonization with resistant or hospital acquired infectious organisms.…”
Section: Chemotherapymentioning
confidence: 99%